2013
DOI: 10.1111/ijlh.12178
|View full text |Cite
|
Sign up to set email alerts
|

Stability of athlete blood passport parameters during air freight

Abstract: Whole blood samples stored in NanoCool devices can be relied upon to remain stable for at least 72 h despite interim air freight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…[30] However, a recent study demonstrated that an optimized instrument calibration of the Sysmex XT-2000i (which is used by more than 30 of the approximately 35 WADA-accredited laboratories), lowered the between-instrument to less than 0.1 %, [30] which is acceptable in anti-doping. Further, ret% has proven to be stable during both storage and transportation [31][32][33][34] as long as the ABP Operating Guidelines are applied, and it has no diurnal variation. [35,36] There are little data available on the effect of exercise on ret%.…”
Section: Reticulocyte Percentage As a Marker For Atypical Blood Profilesmentioning
confidence: 99%
“…[30] However, a recent study demonstrated that an optimized instrument calibration of the Sysmex XT-2000i (which is used by more than 30 of the approximately 35 WADA-accredited laboratories), lowered the between-instrument to less than 0.1 %, [30] which is acceptable in anti-doping. Further, ret% has proven to be stable during both storage and transportation [31][32][33][34] as long as the ABP Operating Guidelines are applied, and it has no diurnal variation. [35,36] There are little data available on the effect of exercise on ret%.…”
Section: Reticulocyte Percentage As a Marker For Atypical Blood Profilesmentioning
confidence: 99%
“…According to our results, standardized and carefully monitored temperature is the condition which quantitatively determines which overall duration of storage is adequate, without risk of analytical deviations due to cell aging‐related lesions. Transport in itself, in effect, does not have any effect on the stability of EDTA‐anticoagulated blood samples . On these basis, we have defined and validated a simple formula, BSS = CAT + 3 × T, that can be used as a laboratory quality index to evaluate the quality of a blood sample in various time and storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical stability of aged samples is also important in consideration of the use of refrigerated and stored specimens as test material for quality control procedures . Other researchers have specifically assessed the stability of blood samples collected for antidoping purposes . All these studies agree that results of blood cell measurements do not significantly change over periods of at least 72 h, provided that blood tubes are appropriately refrigerated prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…vibration, reduced pressure) occurring during air freight. [230] No effect caused by up to 28 h of air transportation time was observed, and blood samples were shown to produce reliable data under routine doping control analytical conditions up to 72 h post-collection.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 96%
“…Besides actual variations in blood parameters, other reasons possibly causing biased test results were investigated such as conditions (e.g. vibration, reduced pressure) occurring during air freight . No effect caused by up to 28 h of air transportation time was observed, and blood samples were shown to produce reliable data under routine doping control analytical conditions up to 72 h post‐collection.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%